Respiratory gas exchange in patients with spontaneous pneumothorax. Issue 4 (July 1968) - Norris, R. M.; Jones, J. G.; Bishop, J. M.
Abstract : Pulmonary gas exchange was studied in 12 patients with spontaneous pneumothorax by measuring the partial pressure of oxygen and carbon dioxide in arterial blood and expired gas when breathing air and 100% oxygen. The arterial oxygen tension was below 80 mm. Hg in nine patients, and the alveolar-arterial difference in oxygen tension was abnormally large in 10, but the physiological dead space was generally normal. There was a positive correlation between the size of the anatomical shunt and the extent of the pneumothorax as measured from the chest radiograph. Calculations indicated that the fall in arterial oxygen tension when breathing air could be fully accounted for by the increased anatomical shunt. After the air had been removed ventilation—perfusion relationships appeared to become more uneven, and the anatomical shunt was greater than would have been expected from the size of the lung. Observations during infusions of acetylcholine suggested that active vasoconstriction in poorly ventilated regions may have occurred to a slight or moderate degree in four out of eight patients.